Community radio and crisis communication: a study on the reach and effectiveness of Peridar Kaala Vaanoli 107.8 MHz. Issue 3 (2nd October 2019) - Selvaraj, Mahalakshmi; Kuppuswamy, Sunitha
Abstract : A community radio (CR) station stands as a lifeline for information and communication to the remote, marginalized and the most vulnerable during natural disasters like the Tamil Nadu Floods in 2015. As a result of this, a license was granted to allow the operation of an emergency community radio station 'Peridar Kaala Vaanoli' ( PKV ) (Tamil words meaning 'Radio in the time of extreme calamity'). This became the first emergency radio station in the country. The current study aims to evaluate the reach and impact of the community radio PKV with broadcast frequency 107.8 MHz in communicating crisis information during the aftermath of the Tamil Nadu Floods, 2015 in Cuddalore district through an interview schedule of the listeners of Peridar Kaala Vaanoli . The study considers the aspects of the socio-economic profile of the listeners, influential factors of listenership and the impact created by the community radio. The respondents were found to be posing socio-economic vulnerability; the factors influencing listenership were communication style, information credibility and educational broadcasts. The psycho-social impact created by PKV includes issue mediation, knowledge empowerment and community development.